EXPLORATORY BEHAVIOR IN MATHEMATICS FOR MIDDLE SCHOOL GIRLS - Aswan Saber Majid (Scholars Digest Publishing, 2024)
This research aims to study the exploratory behavior in mathematics among middle school girls in Maysan Governorate, Iraq. The research sample consisted of (130) female students from the second middle school grade. The exploratory behavior scale was used to collect data. The research recommends the following: - Applying the exploratory behavior scale to students in schools and colleges. -Reducing the fear of mathematics in general. -Increasing the efficiency of teaching and learning. -Encouraging teachers to use exploratory behavior in teaching mathematics. Thr research results showed that: - The female students of the second middle school grade in Maysan do not possess exploratory behavior. -Exploratory behavior in the educational environment does not meet the needs of students effectively to improve the level of academic achievement and achieve the desired goals.
Keywords: exploratory behavior, mathematics, third intermediate, educational environment and efficiency.